2015
DOI: 10.1002/anie.201412209
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyanido(difluorido)phosphates M+[PF2(CN)4]

Abstract: The systematic study of the reaction of M[PF6 ] salts and Me3 SiCN led to a synthetic method for the synthesis and isolation of a series of salts containing the unprecedented [PF2 (CN)4 ](-) ion in good yields. The reaction temperature, pressure, and stoichiometry were optimized. The crystal structures of M[PF2 (CN)4 ] (M=[nBu4 N](+) , Ag(+) , K(+) , Li(+) , H5 O2 (+) ) were determined. X-ray crystallography showed the exclusive formation of the cis isomer in accord with (31) P and (19) F solution NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…Owing to the distinctive physicochemical properties of ILs (wide liquidus range, high redox and thermal stability, negligible vapor pressure, and tunable polarity) and their advantages over organic solvents, classic melts, or solid state reactions, their applications include separation techniques [7,8,9], lubrication [10], electrodeposition [11], acting as electrolytes in photovoltaic devices (e.g., solar cells) [12,13,14], catalysis for clean technology [15,16,17,18], polymerization processes [19], crystal engineering of a wide range of inorganic substances [20,21,22,23,24,25], and syntheses of new inorganic materials in general [23,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. Recently, several comprehensive reviews on syntheses of inorganic compounds in ILs have been published by Taubert [52], Feldmann [28], Dehnen [51], Janiak [42,53], Scrosati and Passerini [48], Morris [54], Mudring [55], Prechtl [56], Zhu [57], Dai [58], and Ruck [23,27,59] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the distinctive physicochemical properties of ILs (wide liquidus range, high redox and thermal stability, negligible vapor pressure, and tunable polarity) and their advantages over organic solvents, classic melts, or solid state reactions, their applications include separation techniques [7,8,9], lubrication [10], electrodeposition [11], acting as electrolytes in photovoltaic devices (e.g., solar cells) [12,13,14], catalysis for clean technology [15,16,17,18], polymerization processes [19], crystal engineering of a wide range of inorganic substances [20,21,22,23,24,25], and syntheses of new inorganic materials in general [23,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. Recently, several comprehensive reviews on syntheses of inorganic compounds in ILs have been published by Taubert [52], Feldmann [28], Dehnen [51], Janiak [42,53], Scrosati and Passerini [48], Morris [54], Mudring [55], Prechtl [56], Zhu [57], Dai [58], and Ruck [23,27,59] among others.…”
Section: Introductionmentioning
confidence: 99%
“…An intensives tudyo nt he reaction of [nBu 4 N][PF 6 ]w ith an excess of Me 3 SiCN (10 equiv) clearly indicated that increasing the reaction temperature above 200 8Cl ed to polymerization of Me 3 SiCN and decomposition of the product, and increasing the excess of Me 3 SiCN also did not lead to further substitution or an increase in the overall yield. [12] For this reason we studied the influence of the cation on the substitution reaction. Surprisingly,w hen we used [Ph 3 C][PF 6 ]i nstead of [nBu 4 N][PF 6 ], an immediate violent reaction occurred at room temperatures on addition of Me 3 SiCN (10 equiv) and resulted in the exclusive formationo ft he [PF 2 (CN) 4 ] À ion as indicated by 19 Fa nd 31 PNMR experiments (Scheme 3, Table 1, and Supporting Information Ta bles S22 and S23).…”
Section: Reaction Of [Ph 3 C][pf 6 ]With Me 3 Sicnmentioning
confidence: 99%
“…For two sets of cations,[ nBu 4 N] + and [nPr 3 NH] + ,w ew ere able to synthesize and fully characterize the corresponding [PF 6Àn (CN) n ] À (n = 0-4) salts (Table 7a nd 4 ]: À32 8C). [12] NMR spectroscopy Generally,w ith respect to NMR experiments, cyanido(fluorido)phosphates are interesting, since all elements of the [PF 6Àn (CN) n ] À ion ( 13 C, 14 N, 15 N, 19 F, and 31 P) are NMR-active. The 19 Fa nd 31 PNMR spectra are depicted in Figures S2-S17 and the shifts and coupling constantsa re listed in Ta bles S22-S23 of the Supporting Information.…”
Section: Meltingp Ointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing ionic liquids (ILs) as reaction media for the (ionothermal) synthesis of inorganic materials has not only allowed their resource‐efficient production, but also lead to the discovery of new compounds . Among the latter are various new bismuth‐transition metal clusters, [RhBi 9 ] 4+ , [ M Bi 10 ] 4+ ( M = Pt, Pd), [Au(Bi 8 ) 2 ] 5+ , [CuBi 8 ] 3+ , and [(RhBi 7 )Br 8 ] (Figure ) , .…”
Section: Introductionmentioning
confidence: 99%